Prevalence of Obsessive-Compulsive Spectrum Disorders in Obsessive-Compulsive Disorder - Siddiqui, Mohammad Aleem (Indian J Psychol Med, 2018)
INTRODUCTION: There is growing awareness of the heterogeneity of obsessive-compulsive disorder (OCD) and of the multiple systems involved in its pathogenesis. Identification of obsessive-compulsive spectrum disorders (OCSDs) may have important implications in the management and prognosis of OCD, but there is a paucity of research in the domain of identification of OCSD in probands with OCD. There are few studies that have examined OCSD in the first-degree relatives (FDR) of OCD patients, some of these were not controlled, and these studies have no final agreements over outcomes, and therefore, this area needs to be further explored. OBJECTIVES: The objective of this study was to assess the prevalence of OCSDs in OCD probands; and its relationship to sociodemographic and clinical variables, comparing each aspect by a control group of schizophrenia probands. MATERIALS AND METHODS: Sixty patients each of OCD and schizophrenia, diagnosed by the Diagnostic and Statistical Manual of Mental Disorders IV Text Revision,[1] above 18 years of age and giving informed consent, were interviewed using the Structured Clinical Interview for OCSD, Yale–Brown Obsessive-Compulsive Rating Scale, Hamilton Rating Scale for Depression, and Hamilton Rating Scale for Anxiety. RESULTS: In OCD group, 22 OCSDs were found in 11 subjects whereas in schizophrenia group, 2 OCSDs (self-injury) were found in two probands. When the two groups were compared in terms of individual OCSDs, there was no significant difference between them. However, when the comparison was made taking into account all OCSDs taken together, it was significantly higher (P = 0.016) in the OCD group compared to the schizophrenia group. CONCLUSION: OCSDs were significantly more in OCD probands as compared to schizophrenia probands. This suggests a familial aggregation of these disorders.